RUSSIAN LANGUAGE IN THE MODERN WORLD: TRADITIONS AND INNOVATIONS IN TEACHING RUSSIAN LANGUAGE IN NATIONAL GROUPS - Zakira Beketovna Nurgizarova (Journal Park Publishing, 2023)
The article discusses the traditions and innovations of teaching the Russian language in Uzbek and foreign language areas of higher education.
Keywords: Russian literary language, language barriers, interpersonal communication, Russian language teaching.